Gender differences in cardiovascular risk factor awareness. Results from the ESC EORP EUROASPIRE V registry. (11th May 2022) - Vynckier, P; Kotseva, K; Gevaert, S; De Bacquer, D; De Smedt, D
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): Fonds voor hartchirurgie - Fonds pour la Chirurgie Cardiaque Background: Risk factor awareness among coronary patients is related to a decreased risk of recurrent coronary events and hence important in the secondary prevention of coronary heart disease (CHD). Whereas previous studies demonstrated gender differences in disfavour of women with regard to patients' risk factor control, little is known about gender differences in patients' risk factor awareness. Purpose: The aim of this study was to document potential gender differences across Europe in patients' risk factor awareness and information provided by healthcare professionals. Methods: Analyses were based on data from the most recent ESC EORP EUROASPIRE V survey (European Survey Of Cardiovascular Disease Prevention And Diabetes, 2016-17). Consecutive patients hospitalized for a first or recurrent coronary event or surgical procedure between 18-80 years old at the time of identification were retrospectively identified in 27 countries. Awareness of risk factor levels were defined as patients' self-reported awareness about their latest weight, waist circumference, blood pressure, total cholesterol, blood glucose levels, and HbA1c levels. Data on risk factor awareness and information provided by healthcare professionals were obtained from patient interviews (6 months to 2 years prior to the date of the study visit). Logistic regression analyses were performed adjusting for age and medical history (stroke, heart failure, and diabetes). Results: Information was available on 8, 261 patients, including 25.8% women. Women were significantly older (65.4 vs. 63.0 years) and were more likely to have a history of stroke (5.3% vs. 3.7%; P=0.002), heart failure (7.6% vs. 5.9%; P=0.006), and self-reported diabetes (33.1% vs. 28.0%; P<0.001). Overall, no significant gender differences were found regarding the information provided by a healthcare professional on overweight, diabetes, and chronic kidney disease, whereas, a higher proportion of women with hypertension (≥140/80 (≥140/85 if diabetes)) (OR=2.07, 95% CI=4.60-2.68) and women with raised cholesterol levels (LDL-C ≥1.8mmol/L) (OR=1.31, 95% CI=1.14-1.51) were informed about their raised risk factor levels. Furthermore, women with obesity were less aware about their actual weight (OR= 0.66, 95% CI=0.52-0.85) and weight target level (OR= 0.66, 95% CI=0.54-0.81) than men. In contrast, no significant gender differences in awareness of waist circumference levels were found in obese patients neither for fasting blood glucose or HbA1c levels in patients with self-reported diabetes. Women with hypertension and those found with raised LDL-C levels were more aware about their target blood pressure level (OR=1.21, 95% CI=1.01-1.46) and actual cholesterol level (OR=1.18, 95% CI=1.02-1.36). Conclusions: Our study reveals only little gender differences in disfavour of women in terms of information provided by healthcare professionals and risk factor awareness.